Social work : an empowering profession - DuBois, Brenda , 1949-; Miley, Karla Krogsrud , 1942- (Boston, Massachusetts : Allyn & Bacon, 2011)
An introductory text taking a discipline approach rather than a social problems approach. Overviews various elements of the field, covering historical and philosophical roots, the professional value base, dimensions of human behavior and social problems, perspectives on diversity, the social service delivery
network, and the social work interventions of practice, policy, and research. Boxes feature contemporary issues, examples, and ethical concerns. This third edition contains new case material and expanded material in areas such as social welfare, child welfare, and gerontological social work. Each chapter reflects and integrates the core competencies in the 2008 Educational Policy and Accreditation Standards (EPAS) set by the Council on Social Work Education (CSWE)
1. Social work: a helping profession -- 2. An evolving profession -- 3. Social work and social systems -- 4. The social service delivery system -- 5. Values and ethics in social work -- 5. Values and ethics in social work -- 7. Diversity and social work -- 8. Empowerment social work practice -- 9. Social work functions and roles -- 10. Social work and social policy -- 11. Social work and poverty, homelessness, unemployment, and criminal justice -- 12. Social work in health, rehabilitation, and mental health -- 13. Social work with families and youths -- 14. Adult and aging services
Includes bibliographical references (p. 421-445) and index
Keywords: Social service; Social service -- Textbooks; Social service -- United States; Social service -- United States -- Textbooks